Thais (Stramonita) rustica (Lamarck, 1822) (Mollusca: Gastropoda: Thaididae), a potential bioindicator of contamination by organotin northeast Brazil (Brazilian Journal of Oceanography, 2004)
The use of antifouling paints containing the biocide compound tributyltin (TBT) has been shown as an inductor of imposex in neogastropods mollusks. Imposex is characterized by the development of male features in females, mainly the appearance of a no functional vas deferens and penis. Samples of Thais rustica were collected in eight sites in the metropolitan area of Natal city, Rio Grande do Norte state, northeast Brazil, and examined for occurrence of imposex, which was found in many females. The higher imposex levels were presented by samples from sites near city harbor.